Dynamic photovoltaic greenhouse: Energy balance in completely clear sky condition during the hot period. (1st May 2016) - Marucci, Alvaro; Cappuccini, Andrea
Abstract: In this study, the energy balance for a prototype dynamic photovoltaic greenhouse was determined for days with completely clear skies during the summer. The rotation of photovoltaic panels along the longitudinal axis was the unique feature of the prototype. Inside the greenhouse, the degree of shading most suitable for the requirements of the crop, the cultivation period, the latitude of the site and the climatic conditions was selected by the rotation of the panels. To avoid energy losses from the reflection caused by unfavourably positioned photovoltaic panels, the panels were provided with highly reflective aluminium mirrors. To evaluate the possibility of using the dynamic photovoltaic greenhouse prototype as a passive cooling system, the energy balance was determined. Based on the results, the use of photovoltaic elements offers an alternative perspective for both the shading of greenhouses and the production of electricity in periods of heat and in areas with a warm climate. With planning that considers the type of crop, geographic coordinates, length of the cultivation period and local weather conditions, the use of this structure can reconcile agricultural production with the production of energy from renewable sources. Highlights: We propose a prototype of dynamic photovoltaic greenhouse with variable shading. We study energy balance on days with completely clear sky. We study energy balance and the internal microclimate with different shading percentages. Data suitable for investigating the structure as a passive cooling system. The rotation of the panels allows you to adjust the internal shading.